The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1128/jcm.06179-11
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Epidemiology of Avian Leukosis Virus Subgroup J in Layer Flocks in China

Abstract: 16/19) of the ALV-J layer isolates displayed less than 92.5% sequence homology to those of the ALV-J broiler isolates, although the transcriptional regulatory elements that are typical of avian retroviruses were highly conserved. Several unique nucleotide substitutions in the env gene, the U3 region, and the E element of most of the ALV-J layer isolates were detected. These results suggested that the env gene, E element, and U3 region in the ALV-J layer isolates have evolved rapidly and were significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 35 publications
(47 reference statements)
2
57
0
Order By: Relevance
“…Immunofluorescence assays showed that the mAb 4A3 could react with the British prototype strain HPRS-103 [1], the American strains ADOLHc1 and ADOL-7501 [27], the early Chinese broiler strain NX0101 [3], and recent Chinese layer strains (HuB09JY03, JL08CH3-1, SD09DP04, HLJ09SH01, LN08SY10) [21] (Fig. 2C).…”
Section: Production and Characterization Of Mabsmentioning
confidence: 94%
See 1 more Smart Citation
“…Immunofluorescence assays showed that the mAb 4A3 could react with the British prototype strain HPRS-103 [1], the American strains ADOLHc1 and ADOL-7501 [27], the early Chinese broiler strain NX0101 [3], and recent Chinese layer strains (HuB09JY03, JL08CH3-1, SD09DP04, HLJ09SH01, LN08SY10) [21] (Fig. 2C).…”
Section: Production and Characterization Of Mabsmentioning
confidence: 94%
“…Because ALV-J has become widespread and has caused great economic losses to poultry in China [21], an effective and rapid diagnostic method for ALV-J infections is urgently needed. Defined B-cell epitopes, which are regions recognized by specific antibodies or B-cell receptors, have become useful tools for the development of diagnostic methods [22].…”
mentioning
confidence: 99%
“…The detection limit of this method was as low as 1 ϫ 10 2 viral DNA copies for each of the three plasmids. The mPCR method was compared with the virus isolation method because virus isolation is considered to be the gold standard for viral detection (10). In animal experiments, the mPCR detected ALVs 2 to 4 days earlier than virus isolation from whole-blood samples and 2 days earlier than virus isolation from cloaca swabs.…”
Section: Discussionmentioning
confidence: 99%
“…No field cases of ALV-J infection or tumors in layer chickens were observed worldwide until 2004 (9-11). However, parent and commercial layer flocks in China have experienced outbreaks of this virus in recent years, causing serious economic losses (10). Thus, ALV-A, ALV-B, and ALV-J are not only the most common but also the most dangerous viruses to the poultry industry.…”
mentioning
confidence: 99%
“…As the spread of the disease is associated with diverse pathotypes and could result in enormous economic losses, ALV-J-induced disease in layer-type chickens has become one of the most important problems facing the global poultry industry. In addition to the fact that the higher incidence of lymphoid leukosis (LL) or erythroblastosis (EB) in susceptible chickens is induced by the ALV subgroups A (ALV-A) and B (ALV-B) (5), ALV-J was also found to be the main cause of ML and hemangioma after a long latent period, as well as a wide variety of other tumors at a lower incidence (6)(7)(8)(9). Further studies have found that virus-and/or cell lineage-specific determinants are also important for tumor development, but the oncogenicity of ALV-J remains unclear.…”
mentioning
confidence: 99%